The Linguistic Moment: From Wordsworth to Stevens - JOSEPH HILLIS MILLER (Princeton University Press, 2014)
The odd status of prefaces, as of titles, epigraphs, dedications, and footnotes, has frequently been observed of late.2 Prefaces are like thresholds, frontiers, gates, or doorways to the infolded text within. Marginal, fencing, framing, liminal, or januarial, they are neither quite inside the work they introduce nor quite outside. They are neither quite part of the work—a contribution to its working, its effective energy of the production of meaning—nor quite not part of it. They may even inhibit or block that working. Prefaces are, precisely, parerga, like those "pamphlets—or 'Parerga' as he called them—by which [Mr. Casaubon, in Middlemarch] tested his public and deposited small monumental records of his march."3 A preface, however, is a peculiar sort of parergon, extra-work beside the work, hors d'oeuvre, not in the sense of being preliminary to the work, anticipatory of it, or adjacent to it while it is being written, but first and last at once. A preface can only be written after the book, and it can only be written by someone with full knowledge of where the book leads the reader, the goal it reaches. On the other hand, a preface is almost the first thing the reader encounters. It is the first step in the journey that will lead her or him to the goal of finishing the book. A preface is both foretaste and aftertaste. Insofar as one must have read the book through in order to understand it, to take that panoramic view of it the preface claims to have, the preface will by definition be incomprehensible or at least partially opaque to the reader who encounters it first, at least until she or he has read the book, at which point she or he will not need the preface. If a preface is like a sign to a bridge, it is simultaneously at both ends of the bridge, or it is like a sign that has Enter on one side and Exit on the other. A preface is magically encountered again and seen in a new light when the reader gets to the other side. A preface is two-faced, like Janus, guardian of portals and patron of beginnings and endings.